2017
DOI: 10.1038/s41598-017-06958-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of Chinese liquor with different ages and prediction analysis based on gas chromatography and electronic nose

Abstract: The economic value of Chinese liquor is closely related with its age. Results from gas chromatograph (GC) analysis indicated that 8 dominant compounds were decreased with the increase of liquor age (0 to 5 years) while ethyl lactate was found to be the most stable dominant compound as no significant change was observed in it during the aging process. Liquor groups with different ages were well-discriminated by principal component analysis (PCA) based on electronic nose signals. High-accurate identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Flavour, as an important quality characteristic of Baijiu , has been widely investigated 18 , 19 . To illustrate the contribution of microorganisms to flavour, bacterial and fungal diversities in Daqu and light-flavour Baijiu fermentation processes were primarily detected both by culture-dependent and culture-independent methods 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Flavour, as an important quality characteristic of Baijiu , has been widely investigated 18 , 19 . To illustrate the contribution of microorganisms to flavour, bacterial and fungal diversities in Daqu and light-flavour Baijiu fermentation processes were primarily detected both by culture-dependent and culture-independent methods 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This is reasonable because the spontaneous chemical oxidation of alcohols to aldehydes or carboxylic acids by dissolved O 2 is a very slow process. 25 , 26 Kilmartin et al have reported that the polyphenols in wine are the redox-active compounds that are easily oxidized at metal or carbon electrodes. 27 However, in the case of Baijiu, it has been reported that the alcohols in Baijiu can be oxidized by the oxygen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…27 However, in the case of Baijiu, it has been reported that the alcohols in Baijiu can be oxidized by the oxygen. 25 , 26 Thus, we next consider the influence of electrochemical oxidation on the alcohols in Baijiu.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Rhizopus oryzae has high amylase production capacity, which can degrade starch in sorghum, and is widely used in koji and Baijiu brewing [34]. It affects Baijiu avour by produce glycerol, lactic acid, enzymes and volatile compounds, such as ethanol, 2-methyl-1-butanol, and 3-methyl-1-butanol [35]. Aspergillus produce a wide spectrum of proteolytic and other lytic enzymes, playing an important role in sacchari cation of starch and protein hydrolysis in sorghum [36].…”
Section: Discussionmentioning
confidence: 99%